Microstructure and Mechanical Properties of Inconel718–NiCrAlY Composites Prepared by Laser Engineered Net Shaping. Issue 4 (21st February 2018) - Zhang, Guohui; Yan, Shuai; Niu, Fangyong; Ma, Guangyi; Wu, Dongjiang; Guo, Dongming
Abstract : Near‐defect‐free block Inconel718‐NiCrAlY composites prepared by laser engineered net shaping are investigated in this study. XRD, SEM, and EDS are applied to analyze the phase composition and microstructure characteristics. The mechanical properties are evaluated by microhardness tester and friction‐wear tester. The results show that NiAl brittle intermetallic compounds precipitate in the matrix when NiCrAlY content reaches 60% or more. With the increase of NiCrAlY ratio, the distribution of NiAl changes from intergranular precipitation to intragranular precipitation, and the dendrites growth directions become chaotic. The microhardness of composites improves as the NiCrAlY content rises, reaching to 419 HV for 100%NiCrAlY, and solid solution strengthening has better strengthening effect on microhardness than precipitation strengthening. The wear loss has a clear decrease only when 80% or more NiCrAlY is added, with the maximum wear loss drop of 15.66% for 100%NiCrAlY. The wear mechanisms change from the coexistence of adhesive wear and abrasive wear to mainly abrasive wear with micro brittle fractures when NiCrAlY content is high. Abstract : Different ratios of Inconel718–NiCrAlY composites are prepared by Laser engineered net shaping. With NiCrAlY content rising, NiAl precipitates, and changes from intergranular precipitation to intragranular precipitation. Solutions strengthening and precipitation strengthening contributes to early sharp increase and latter slight increase of microhardness, respectively. Wear loss drops maximum 15.66% with the increase of NiCrAlY content, and the wear mechanisms change.